Teaching styles of Malaysian ESL instructors: an investigation into current practices and implications to English Language Teaching (ELT) - Thang, Siew Ming; Wong, Fook Fei (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2005)
Research studies (Felder and Silverman, 1988; Lawrence, 1993; Oxford, Ehrman and Lavine, 1991; Schmeck, 1988) have pointed out the problems associated with serious mismatches always possible for the teaching styles of teachers to match that of students, considering that in a class there are students with a variety of learning styles. However, it is crucial for ESL (English as Second Language) teachers to be aware of the students' different learning styles and to adapt their teaching styles accordingly (Kinsella, 1995; Kinsella and Sherak, 1998; Thang, 2003). In addition, it is crucial for ESL teachers to possess knowledge of current theories and thinking in ESL teaching and learning and to help students inculcate strategies and processes for effective and autonomous language learning (Oxford, 1990; Oxford and Ehrman, 1995; Rossi-Le, 1995). This study is undertaken on a group of ESL instructors teaching English for Specific Purposes (ESP) courses in a public university in Malaysia to find out (1) to what extent ESL instructors apply current theories and thinking on ESL teaching and (2) to what extent they consider the learning styles of their students in their teaching and help their students to be aware of the appropriate language learning strategies and processes for autonomous language learning. A questionnaire was used to collect data for the study and the results were analyzed quantitatively. Pedagogical implications of the findings would also be discussed.